Analysis of the Application of E-Commerce Applications in Increasing Sales Revenue at PT. United Tractors Tbk. Alvin Krisdian, Shela, Jenifen, Juliani, Financial Management Study Program, Faculty of Economics Prima University of Indonesia - Alvin Krisdian; Jenifen; Shela; Rafida Khairani (Jurnal Mantik, 2022)
The purpose of this research is to understand the income before and after implementing the e-commerce system at PT. United Tractors Tbk. the type of research is "Qualitative" which is descriptive based on the level of explanation and the place of research at PT. United Tractors. The research variables are income & e-commerce sales system, the data in the research is primary data. The technique of obtaining documentation data, using qualitative analysis methods to present detailed explanations of income before and after, PT. United Tractors' income in 2013 amounted to Rp. 51,012,385, while in 2014 the revenue of PT. United Tractors was Rp. 53,141,768 at a percentage of 4.01%. Income PT. United Tractors 2013-2014 found a change in income that is not bad and significant, After PT. United Tractors using e-commerce in 2015 the income earned Rp. 49,347,479 there was a decrease until 2016 to 8.36% with a total of Rp. 45,539,238, In 2017 the income was Rp. 64,559,204 experienced an increase of up to 29.46% and in 2018 it increased by 29.46% with an income of Rp. 84,624,733, There was a decrease in 2019 of 0.23% of Rp. 84,430,478 and fell 39.91% to Rp. 60,346,784 in 2020.